Development of Thai Words Reading and Spelling Skills by Using Games for Prathom Suksa 1 Students, Ban Rin Luang School - Thiratpanyachoti, Chirapriya; Wichalai, Anongsiri; Pothasin, Warunee (MCU Haripunchai Review, 2026)
The objectives of this research were to 1) create and evaluate the validity of the game-based learning management plan for the development of Thai spelling reading and spelling in the Thai language learning content group, and 2) compare the reading achievement in the Thai language learning content group using games during before and after school for Grade 1 students of Ban Rin Luang School. The sample consisted of 20 students in Grade 1 in the 1st semester of the 2022 academic year, and the tools used in the study included 5 game-based learning management plans for Grade 1 students of 3 hours each, 17 hours each before and after the exam for a total of 5 weeks. The results showed that: 1) Creation of a learning management plan using game-based teaching methods for grade 1 students who have passed the appropriateness and accuracy assessment. It was found that the plan was at the most appropriate level (,x.= 4.80). It can be used to improve students’ reading and writing, including learning standards, indicators, and essences. Learning Objectives and Learners’ Important Competencies Desirable Attributes, Learning Content, Methods of Organizing Learning Activities, Learning Materials and Resources, Measurement and Evaluation Opinion of school administrators Record of the results after the learning management and appendices 2) The achievement of reading and spelling skills using the game-based learning management plan for Grade 1 students showed that the average before school was 10.7, or 35.66 percent, the standard deviation was 1.37, and the achievement of reading skills after school was 1.37. The average score was 18.25, or 60.83%, and the standard deviation was 2.07. The average score increased by +7.55. Useful suggestions for this research that 1) Apply the teaching and learning model of reading and spelling using games to other students who also have problems reading Thai spelling. 2) Compare the game-based Thai spelling teaching model with other forms of reading and spelling learning to compare the development of Thai spelling learning management to be more effective and successful.